Composting system improvement by life cycle assessment approach on community composting of agricultural and agro industrial wastes - Aziz, Rizki -; Chevakidagarn, Panalee; Danteravanich, Somtip - (Indonesian Journal of Environmental Management and Sustainability, 2018)
In order to improve a community composting system, three scenarios have set based on the critical points of initial system from sensitivity analysis result of Life Cycle Assessment of community composting system of agricultural and agro industrial wastes composting. Sensitivity analysis of initial system revealed two critical points that used as consideration on setting of improvement system scenarios. On initial system, composting process contributed the highest impact potency on acidification, eutrophication, global warming, and photochemical oxidation, while distribution was responsible for the highest impact on human toxicity potential. By comparison of initial composting system with three improvement scenarios, it found that the third improvement scenario (SC3) was the best scenario that recommended to be implemented. SC3 promoted application of compost blanket for gases emission reduction of compost pile, and substitution diesel fuel of pick-up with CNG fuel for transportation emission reduction. This scenario reduced impact of initial composting system by 29% with the highest impact reduction was on global warming potential by 54%.